(untitled) (Research, Society and Development, 2023)
This research aims to identify in the literature about nursing care during the blood transfusion process in cancer patients. This is an integrative literature review, with a descriptive exploratory approach of a qualitative nature. Guided by the research question: What is the evidence on nursing care in blood transfusion to cancer patients? The search took place in the following databases: Latin American and Caribbean Literature in Health Sciences (LILACS), Medical Literature, Analysis and Retrieval System Online (MEDLINE), Cochrane Central Register of Controlled Trials of the Cochrane Library and in the Nursing Database (BDENF) and Scientific Electronic Library Online (SCIELO). Conducted between the period 2016 to 2021. Seventeen scientific productions were selected to compose this literature review. The critical analysis of the studies made it possible to create two categories for discussing the results. Category 1- Nursing Assistance; Category 2- Educational technology to mediate nursing care during the blood transfusion process in cancer patients. According to the literature review, it was identified how nursing care for cancer patients during blood transfusion has been carried out in health institutions and the need to use educational technologies during the blood transfusion process in hospitalized patients was discussed.